2018
DOI: 10.1093/annonc/mdy061
|View full text |Cite
|
Sign up to set email alerts
|

RAS mutation analysis in circulating tumor DNA from patients with metastatic colorectal cancer: the AGEO RASANC prospective multicenter study

Abstract: Clinicaltrials.gov, NCT02502656.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
128
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(149 citation statements)
references
References 18 publications
17
128
1
3
Order By: Relevance
“…Although the amount of cfDNA has been reported to be associated with the clinical factors, which were suggestively correlated with tumor burden such as metastasis and tumor markers, we found that ctDNA level is likely to be more correlated with those factors than cfDNA (Table ). We observed significant association of ctDNA level with liver metastasis and sum of the tumor diameter in metastatic sites, which were commonly reported to be strongly associated with ctDNA level . While the controversial or null association of ctDNA level with the lung, lymph node and peritoneal metastasis, tumor markers, primary tumor location, and number of metastatic organs has been reported, we observed significant association between ctDNA level and lymph node metastasis, number of metastatic organs, and tumor markers (CEA, CA19‐9, and LDH).…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Although the amount of cfDNA has been reported to be associated with the clinical factors, which were suggestively correlated with tumor burden such as metastasis and tumor markers, we found that ctDNA level is likely to be more correlated with those factors than cfDNA (Table ). We observed significant association of ctDNA level with liver metastasis and sum of the tumor diameter in metastatic sites, which were commonly reported to be strongly associated with ctDNA level . While the controversial or null association of ctDNA level with the lung, lymph node and peritoneal metastasis, tumor markers, primary tumor location, and number of metastatic organs has been reported, we observed significant association between ctDNA level and lymph node metastasis, number of metastatic organs, and tumor markers (CEA, CA19‐9, and LDH).…”
Section: Discussionsupporting
confidence: 42%
“…We observed significant association of ctDNA level with liver metastasis and sum of the tumor diameter in metastatic sites, which were commonly reported to be strongly associated with ctDNA level. 20,34,35 While the controversial or null association of ctDNA level with the lung, lymph node and peritoneal metastasis, tumor markers, primary tumor location, and number of metastatic organs has been reported, 20,34,36,37 we observed significant association between ctDNA level and lymph node metastasis, number of metastatic organs, and tumor markers (CEA, CA19-9, and LDH). Although different sample size and sampling bias may cause these discordant results, the above associations should be further validated by using a larger number of samples.…”
Section: Discussionmentioning
confidence: 54%
“…In the RASANC prospective study, RAS status was determined using next-generation sequencing (NGS) on 412 paired plasma and tumor samples. An excellent concordance (kappa coefficient 0.71 [95% CI: 0.64-0.77] and accuracy 85.2% [95% CI: 81.4-88.5]) were found between plasma and tissue [10]. These different studies allowed considering the use of liquid biopsy but with a necessity of tumor tissue testing in case of negative results in plasma.…”
Section: Introductionmentioning
confidence: 80%
“…Several studies have demonstrated a high concordance between mutational profiles of candidate genes in matched tumor and plasma DNA samples from mCRC patients. ctDNA should be an easy and reliable tool for targeted therapy introduction [8][9][10]. RAS mutations have been assessed using BEAMing in 146 plasma samples from patients with mCRC in the study published by Grasselli et al; 48% of their samples were found with a mutant allele fraction from 0.01% to 1% [33].…”
Section: Discussionmentioning
confidence: 99%
“…Head-to-head retrospective series reported a concordance rate higher than 90% between results of tissue and plasma analyses [72,73,74,75,76,77,78]. Noteworthy, not only intrinsic analytical factors, but also a number of clinical and pathological variables, including sites of metastases, disease burden, and tumor histology, may influence the release of ctDNA by tumor cells, thus affecting results of plasma testing.…”
Section: Personalizing the Use Of Anti-egfrs: A Potential Applicatmentioning
confidence: 99%